Extended surgical safety margins and ulceration are associated with an improved prognosis in pleomorphic dermal sarcomas. (27th March 2019) - Persa, O.D.; Loquai, C.; Wobser, M.; Baltaci, M.; Dengler, S.; Kreuter, A.; Volz, A.; Laimer, M.; Emberger, M.; Doerler, M.; Mauch, C.; Helbig, D.
Abstract: Background: Pleomorphic dermal sarcomas (PDS) are frequent UV‐induced sarcomas of the skin of intermediate grade malignant potential. Despite the fact that PDS have a noteworthy potential to recur (up to 28%) as well as to metastasize (up to 20%), there are no specific clinical guidelines with respect to follow‐up these patients. Moreover, little is known about clinical, histological or molecular prognostic factors in PDS. Objective: The aim of the present study was to identify risk factors to predict relapse in a large multicentre sample cohort of PDS which could aid to optimize personalized treatment recommendations regarding surgical safety margins and adjuvant radiotherapy. Methods: Patients with a diagnosis of PDS were selected from nine European institutions based on the histopathologic criteria described by Fletcher. Clinicopathologic and follow‐up data were collected and statistically analysed calculating univariate hazard ratios with 95% confidence intervals by use of the Cox proportional‐hazards model and a significance level of P < 0.05. Patients with an incomplete excision of the tumour were excluded. Results: Univariate Cox regression analysis of possible prognostic factors for progression‐free survival (PFS) performed in 92 patients revealed that an excision margin of <2 cm is significantly associated with relapse of PDS [hazard ratio 4.478 (95% CI 1.536–13.055), P = 0.006]. Ulceration of the tumour was associated with a significantly better prognosis [0.396 (0.174–0.904), P = 0.028] whereas adjuvant radiotherapy did not reach statistical significance to improve prognosis in patients with PDS [0.775 (0.231–2.593), P = 0.679]. Gender, age, immunosuppression, intratumoural necrosis, tumour location, vertical thickness or horizontal diameter did not significantly influence PFS in PDS. Conclusion: We identified surgical safety margins of <2 cm and absence of ulceration as risk factors for relapse in patients with PDS. These findings may be implemented into both the primary treatment as well as the further monitoring of patients with PDS.